Effects of Dietary Supplementation of Prosopis Africana (African Mesquite) Essential Oil on the Growth Performance, Nutrient Retention and Oxidative Stress Indices of Broiler Chicken - Alagbe J. O; Agubosi O.C.P; Oluwafemi R.A (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research was undertaken to evaluate the effects of dietary supplementation with Prosopis africana essential oil on the growth performance, nutrient retention, and oxidative stress indices of broiler chickens. Improvements in body weight gain and feed conversion ratio (P˂0.05) were observed in birds fed PAOs compared to the other treatments. The mortality rate was highest in T1 (5.33 %) followed by T2 (3.02%) and T3 (1.00%) (P˂0.05). Dressing percentage and weights of organs were significantly (P˂0.05) influenced by the treatments, except the weights of kidney, spleen, pancreas, and busra (P˃ 0.05). Dry matter and crude protein digestibility were highest in T3 through T6, intermediate in T2, and lowest in T1 (P˂0.05). Malondialdehyde, catalase, glutathione peroxidase, reduced glutathione, and superoxide dismutase were significantly (P˂0.05) different among the treatments. Conclusion: It was concluded that the dietary supplementation of PAOs up to 800 mg/kg in broiler chickens could arouse their appetite, translating to higher weight gain, increased secretion of enzymes in the gastro-intestinal tract, and a reduction of free radicals.